Phytochemical Screening and Isolation of Bioactive Compounds from the Ethyl Acetate Extract of Indigofera nummulariifolia - Abubakar, Abdulkadir; Abubakar, Samaila; Kwaji, Andrew; Mohammed Adam, Ibrahim (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Indigofera is the third-largest genus in the family Fabaceae and consists of approximately 750 species, Indigofera numulariifolia, a species within this genus is an annual herb or shrub that is widely distributed throughout tropical and subtropical regions of the world including Nigeria. In ethno-medicine, it is used to treat liver ailments and some viral infections. In this study, the pulverized plant sample was subjected to cold maceration to afford the crude extracts of n-hexane, dichloromethane, ethyl acetate, and methanol. Phytochemical screening of crude extracts was carried out according to standard procedures while the antibacterial activity was assessed using the agar well diffusion method against Escherichia coli, Salmonella typhi, Pseudomonas aeruginosa and Staphylococcus aureus. Isolation of bioactive compounds from the ethyl acetate extract was carried out using open column chromatography and the pure isolates were characterized using IR and GCMS in comparison with the literature. Phytochemical screening of crude extracts were carried out according to standard procedures while the antimicrobial activity was assessed using agar well diffusion method against Escherichia coli, Salmonella typhi, Pseudomonas aeruginosa and Staphylococcus aureus. Purification of the crude extract was done on open column chromatography and characterized using IR and GCMS. The results of phytochemical screening revealed the presence of Saponins, flavonoids, tannins, and steroids. The extracts also showed antimicrobial activity with inhibition zones in the range of 6-20 mm, where the highest activity was recorded against E. coli with a zone of inhibition of about 20 mm. Meanwhile, results from the GC-MS analysis of one of the isolated compounds, revealed the presence of six fatty acid derivatives obtained as a single isolate from the n-hexane ethyl acetate mixture in a ratio of 95:5. These findings enrich the understanding of Indigofera numulariifolia's chemical composition and highlight its potential bioactive constituents.